The Role Of Strategic Control In Crises - زاهر , بسام; اسبر , لمى; عباس, نيروز (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This study aimed at assessing the role of strategic control in banking crises in private banks in Lattakia and the importance of the relationship between them, and for this purpose the researcher formulated the necessary assumptions and using the deductive analytical approach as the researcher distributed the questionnaire to the private banks studied and was done Using the comprehensive survey method and analyzing the results using the statistical spss program. The researcher reached several results, the most important of which was the existence of a direct relationship between strategic control and the management of banking crises, where the value of the correlation coefficient reached (0.445), which is weak The researcher recommended a number of recommendations, the most prominent of which was to strengthen the foundations and foundations necessary for the success of both strategic control and crisis management, by providing banks with trained and trained human cadres, Provide the necessary material and moral support to carry out the monitoring process effectively, including responding to the crisis before it occurs.